The formation of heroes and the myth of national identity. Issue 6 (3rd June 2021) - Parry, Keith D.
Abstract: This paper discusses sports hero formation in relation to national identity, arguing that it can be a critical component of the development of a hero. A netnographic approach, that encompassed a number of virtual spaces and methods of analyses, was utilised to examine the formation of sports heroes within the setting of a new professional sports team. Drawing upon the work of Joseph Campbell and Orrin E. Klapp, it contextualises the sporting hero in the wider narratives of hero typologies. It argues that the formation of sports heroes is shaped by established notions of national identity and longstanding mythological archetypes rather than heroes' personal traits or deeds. Universal hero myths, furthermore, provide recognised narratives that frame the emergence of new heroes in otherwise very different societies.